Prevalence of epilepsy in the onchocerciasis endemic middle belt of Ghana after 27 years of mass drug administration with ivermectin - Kenneth Bentum Otabil; Blessing Ankrah; Emmanuel John Bart-Plange; Emmanuel Sam Donkoh; Fiona Amoabil Avarikame; Fredrick Obeng Ofori-Appiah; Theophilus Nti Babae; Prince-Charles Kudzordzi; Vera Achiaa Darko; Joseph Ameyaw; Joseph Gyekye Bamfo; Raji Abdul Sakibu; et al. (BMC, 2023)
Abstract Background In onchocerciasis-endemic areas with high ongoing Onchocerca volvulus transmission, a high prevalence of epilepsy has been reported. This study aimed to determine the prevalence and clinical characteristics of epilepsy in the Bono Region of Ghana following 27 years of implementation of ivermectin mass drug administration (MDA). Methods Between October 2020 and August 2021, cross-sectional surveys were conducted in nine communities in the Tain District and Wenchi Municipality of the Bono Region of Ghana. In the first stage, a random door-to-door approach was used to screen the population for epilepsy using a pre-tested questionnaire. Persons suspected of having epilepsy were invited for a second-stage neurological examination for case verification. Community O. volvulus microfilarial infection status and Ov16 seropositivity were also determined. Ninety-five confidence intervals (95% CI) for prevalence values were calculated using the Wilson Score Interval. Results Of the 971 participants, 500 (51.5%) were females, and the median age (interquartile range) was 26 (15‒43) years. Fourteen participants (1.4%, 95% CI: 1.0‒2.0) were diagnosed as having epilepsy with generalized seizures being the most frequent seizure type (85.7%, 12/14). The overall microfilarial prevalence of O. volvulus was 10.3% (November 2020) and 9.9% (August 2021); the Ov16 seroprevalence was 22.2% (June 2021). Only 63.2% took ivermectin in the last round of MDA distribution in March 2021. Conclusions The 1.4% prevalence of epilepsy in the Bono region is similar to the median epilepsy prevalence in sub-Saharan Africa. However, the persistent microfilarial prevalence and low ivermectin study coverage call for the Ghana Onchocerciasis Elimination Programme to step up its efforts to ensure that the gains achieved are consolidated and improved to achieve the elimination of onchocerciasis by 2030. Graphical Abstract